Differences in linguistic and psychological characteristics between suicide notes and diaries - Kim, Kyungil; Choi, Sunhee; Lee, Joohyung; Sea, Jonghan (Journal of General Psychology, 2019)
The objective of this study was to explore linguistic and psychological differences in suicide notes and the diaries of non-suicidal people. Fifty-six suicide notes and 56 personal diary entries were analyzed to provide basic descriptive data on linguistic and psychological variables using the Korean Linguistic Inquiry and Word Count Program. The results revealed that the two groups noticeably differed—suicide notes had more words or phrases per sentence; fewer modifiers, numerals, and affixes/suffixes associated with logically elaborated sentences; and more first- and second-person pronouns than the diaries of non-suicidal individuals. Suicide notes also used fewer positive words and future tense verbs, as well as more negative, sadness/depression-related words. Inter-correlations between the linguistic and psychological domains revealed some heterogeneity between the groups. Further research is needed on the practical applications of this study.
Keywords: Adult; Diaries as Topic; Female; Humans; Linguistics; Male; Suicide; Diaries; language pattern; Linguistic Inquiry and Word Count; LIWC; suicide note